2022
DOI: 10.1097/njh.0000000000000869
|View full text |Cite
|
Sign up to set email alerts
|

Palliative Care for Patients With Heart Failure

Abstract: Palliative care should be integrated into routine disease management for all patients with serious illness, regardless of settings or prognosis. The purposes of this integrative review were to identify the features of randomized controlled trials for adult patients with heart failure and to provide basic references for the development of future trials. Using Whittemore and Knafl's integrative literature review method, comprehensive searches of the PubMed, Cochrane Library, CINAHL, EMBASE, and Korean databases … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 33 publications
0
4
0
Order By: Relevance
“…When organizing the selected studies, the need for the inclusion of PC in medical education becomes clear. The above studies show that none of the institutions had this discipline regularly included in their curriculum, despite its importance, as the teaching of palliative care is being recognized worldwide (Who, 2002;Brown et al, 2018, Kim et al, 2022.…”
Section: Resultsmentioning
confidence: 99%
“…When organizing the selected studies, the need for the inclusion of PC in medical education becomes clear. The above studies show that none of the institutions had this discipline regularly included in their curriculum, despite its importance, as the teaching of palliative care is being recognized worldwide (Who, 2002;Brown et al, 2018, Kim et al, 2022.…”
Section: Resultsmentioning
confidence: 99%
“…In the context of HF, PC involves considering combined physical, psychosocial, and environmental factors, such as the use of pacemakers and implantable defibrillators, the unpredictable prognosis of HF, and the perception of overall disease management. 13 A review of selected PC studies in HF showed that life expectancy is 1 of the main considerations in referral to PC services, with additional criteria including New York Heart Association (NYHA) classification and Ejection fraction (EF) value. 13 PC intervention improves the QOL, and current society guidelines recommend early PC integration in HF management, but it remains underutilized in practice.…”
Section: The Concept Of End-of-life and Palliative Carementioning
confidence: 99%
“…13 A review of selected PC studies in HF showed that life expectancy is 1 of the main considerations in referral to PC services, with additional criteria including New York Heart Association (NYHA) classification and Ejection fraction (EF) value. 13 PC intervention improves the QOL, and current society guidelines recommend early PC integration in HF management, but it remains underutilized in practice. 14 It is appropriate at any age and stage of a serious illness and can be provided with curative treatment.…”
Section: The Concept Of End-of-life and Palliative Carementioning
confidence: 99%
“…These goals should prioritize the management of symptoms and respect the patient's preferences. They should be accessible from diagnosis to the end of life, and a multidisciplinary approach with effective coordination between specialists, primary care, and PC physicians is crucial ( 34 ) [ Figure 5 ( 35 )].…”
Section: How Do We Identify Patients With Cardiorenal Disease Needing...mentioning
confidence: 99%